The Relationship Of Work Stress With Lower Back Pain Complaints In Dentists In Jambi City - Rini, Willia Novita Eka; Aswin, Budi; Putra, Ashar Nuzulul; Istarini, Attiya (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: Work stress is one of the factors causing complaints of lower back pain. Work stress has a negative impact on a person's physical and psychological health. Dentists who experience ongoing stress will usually experience complaints of low back pain. Pain can increase during prolonged activities. Increased pain can be felt due to psychological conditions and an unsupportive environment. The aim of this research is to determine the relationship between work stress and complaints of lower back pain among dentists in Jambi City Method: This research is a quantitative study using an analytical observational design with a cross sectional approach. Respondents in this study were 134 dentist taken randomly. Data collection used the Oswestry Dissability Index (ODI) questionnaire to measure complaints of low back pain, the Perceive Stress Questionnaire (PSQ) to measure work stress. Data analysis uses statistical correlation tests. Results: The results of the statistical correlation test show that the work stress variable (p= 0.006) Conclusion: There is a positive correlation between the work stress variable and the lower back pain complaint variable among independent practicing general dentists in Jambi City.